Kompetensi Wirausaha: Pengaruhnya Bagi Pertumbuhan Usaha Kecil Dan Hubungannya Dengan Tingkat Pendidikan Formal? - Zulkarnain (Jurnal Aplikasi Manajemen, 2009)
One of several effort to developing small business is related to have entrepreneurial competencies. The purpose of this research is, firstly, to clarify the effect of cognitive, leadership, knowledge, and human resources competencies toward small business growth secondly, to clarify the correlation among the dimension of its' competences and the levels of formal education. Research findings: firstly, cognitive and knowledge competencies have a positive effects to increasing small business growth, but not significantly. While, human resources have a negative effect and not significant toward small business growth. In the other, the effect of leadership competency is significant, but have a negative effect. Secondly, the levels of formal education have not correlated with cognitive and knowledge competencies, but correlated with leadership and human resources competencies. Research finding indicates that need to explore the other competency characteristics for small business growth and important to give small entrepreneur any non formal education e.g. training that to fit for their practical small business.